The influence of the China GLIM standards on the diagnosis of malnutrition in patients with hematopoietic stem cell transplant - Guo, Feng; Min, Liu; Chengyuan, Li; Hong, Liu; Meng, Wang; Chenyi, Tang; Jinru, Wu; Wei, Wu; Hua, Liu (Frontiers in Nutrition, 2023)
Background: Muscle related indicator is removed from Global Leadership Initiative on Malnutrition (GLIM) criteria implemented in China for many reasons. Hematopoietic stem cell transplant patients are all at nutrition risk, who can enter into the second step of GLIM, so they are suitable for learning the diagnosing malnutrition significance between primary GLIM and GLIM-China criteria. So this article aims to explore the role of muscle mass in the diagnostic criteria of malnutrition, and effects of GLIM- China for diagnosing malnutrition. Methods: Ninety-eight hematopoietic stem cell transplant (HSCT) inpatients were recruited. Nutritional risk was assessed by Nutritional Risk Screening 2002 (NRS-2002). The appendicular skeletal muscle mass (ASMI), fat-free mass index (FFMI) was determined with bioelectrical impedance analysis (BIA) method. Malnutrition is defined by GLIM-China, GLIM and PG-SGA. And we use Erythrocyte Sedimentation Rate (ESR) and C-Reactive Protein (CRP) to assess inflammation in GLIM and GLIM-China. The correlation or consistency among ASMI, FFMI, ESR, CRP, GLIM-China, GLIM and PG-SGA were conducted respectively. Results: One hundred percent instead of the patients had nutritional risk. The magnitude of malnutrition via PG-SGA, GLIM and GLIM-China was 75.5%, 80.6% and 64.3%. GLIM-China and PG-SGA showed the same performance (p =0.052 v.s. 1.00) and agreement (Kappa=0.404 v.s. 0.433, p <0.0001) with FFMI. Consistency was noted between ASMI and PG-SGA in the assessment of malnutrition (p =0.664) with good agreement (Kappa=0.562，p =0.084). ASMI and FFMI could determine the muscle mass reduction that could not be determined by BMI, albumin (ALB), pre-albumin (pre-ALB); 34% of GLIM-China (-) patients were with low ASMI, and 40% with low FFMI; 30.0% of patients with PG-SGA (<4) still have low ASMI, and 38.2% have low FFMI. Conclusion: If only the PG-SGA scale is used as a diagnostic criterion for evaluating malnutrition, a large proportion of patients with reduced muscle mass will be missed, but more muscle loss patients will be missed via GLIM-China. Muscle related indicators will be helpful for diagnosing of malnutrition.